Cell fate conversion—from the viewpoint of small molecules and lineage specifiers. (September 2016) - Zhao, T.; Li, Y.; Deng, H.
Abstract : Mammalian development was generally considered a naturally unidirectional and irreversible process. However, pioneering work of recent decades has highlighted the plasticity of mammalian cells and implied the possibilities of manipulating cell fate in vitro. Pluripotent stem cells, which hold great potential for regenerative medicine, have been shown to be reprogrammed from differentiated cells either by somatic cell nuclear transfer or by ectopic expression of pluripotency factors. Nevertheless, it remained unknown whether the reprogramming could be accomplished without pluripotency genes. Recent studies show that lineage specifiers play an important role in orchestrating the process of restoring pluripotency by replacing pluripotency‐associated transcription factors. Moreover, a combination of small molecules enables the acquisition of pluripotency from somatic cells without any transgenes, offering a tractable platform to precisely dissect the induction and maintenance of cell identity. Here, we will discuss recent scientific advances regarding the cell fate conversion mediated by small molecules or lineage specifiers, especially in the chemically induced somatic cell reprogramming process, and will provide new insights into the intermediate plastic state and "seesaw model" established by chemical approaches during reprogramming.